(untitled) (Bangladesh Journal of Psychiatry, 2022)
Psoriasis is one of the established chronic dermatological disorders which exacerbate and triggers in stressful life condition. Sometimes it may cause disfigurement that enhances stress. In long run majority of patients get depressed and also show symptoms of anxiety and depressive disorder. This was a cross sectional study, conducted in the department of psychiatry in collaboration with the department of dermatology and venereology of Sylhet MAG Osmani Medical College Hospital, Sylhet, Bangladesh during the period from January 2013 to December 2013 to evaluate the psychiatric morbidity among the psoriasis patients and healthy controls and compare with them. For this purpose, 50 patients with psoriasis of 18 years to 65 years of age were included and categorized as group A where another 50 age and sex matched healthy individuals were included as group B by consecutive, convenient (non-probability) sampling technique. Patients having any past or family history of psychiatric disorder, substance abuse, history of any chronic medical illness, history of long term corticosteroid therapy and obese patients were excluded from the study. After taking informed consent respondents were interviewed using data collection sheet containing socio-demographic and other information which was structured and fix response type. A General Health Questionnaire (GHQ) 12 Bangla version was supplied to the patients and advised to fill up the questionnaire. Those who scored 15 or above points were further evaluated by mental state examination and Diagnostic and Statistical Manual of Mental Disorders (DSM) IV Text Revision (TR) criteria for the diagnosis of psychiatric disorders. All psychiatric disorders were diagnosed clinically and verified by consultant psychiatrist. Ethical issues were maintained properly and an informed written consent was taken from every patient. After collecting data, editing was done manually and was analyzed with statistical package for social sciences (SPSS) version 21. The results showed that, the mean age of the respondents was 36.5 (SD±13.5) and control 36.0 (SD±14.4) years which was almost identical to control group (p=0.914). Psychiatric morbidity was most frequent in psoriasis group (62.0%) as compared to control group (20.0%) (p<0.001). The most common psychiatric disorder was major depressive disorder (32.0%) followed by generalized anxiety disorder (18.0%), dysthymic disorder (6.0%), somatoform disorder not otherwise specified (NOS) (4.0%) and adjustment disorder (2.0%). The results of this study suggest that a significant number of patients with Psoriasis suffer from psychiatric disorder than healthy control group. Bang J Psychiatry 2022;36(2): 27-34